PERANCANGAN MOTION GRAPHIC UNTUK MEDIA PROMOSI MERCHANDISE SOYL BALI STUDIO - Wira Palguna, I Putu Adi; Pageh Wibawa, Arya; Tri Narulita, Eldiana (Program Studi Desain Komunikasi Visual, 2024)
SOYL Bali Studio is a media partner that operates in the music industry and creates podcasts and live sessions in the form of videos uploaded on the YouTube platform and is also active on Instagram to share the activities they are carrying out and is now starting to develop with the addition of several divisions such as SOYL Merch and SOYL Records. The merchandise that SOYL made was previously intended only as souvenirs for guest stars, and now the merchandise wants to be sold to the public and SOYL podcast viewers, so the role of innovative promotional media is needed in the creative and business industries to build brand image, attract customer attention , and survive in tough competition. To overcome this competition, new and different promotional content is needed compared to the use of photos as content that is commonly used, the use of animated motion graphics as a form of promotional media can be different and can be a special attraction. Motion graphics are a combination of moving images and audio-visual elements, such as text, sound, illustrations, photos and videography. In designing motion graphics, it starts from the exploration, improvisation, and formation stages. This design includes the use of a creation method based on the Hawkins concept and its application in designing motion graphics for promotional media for SOYL Bali Studio merchandise. In addition, it discusses the role of management in the creative process at SOYL Bali Studio, with a focus on the effective use of human and other resources. Study/Independent Project at SOYL Bali Studio combines learning about management and creating motion graphic promotional content to support the promotion of SOYL Merch merchandise on social media.